Wood-derived biochar as thick electrodes for high-rate performance supercapacitors - Yan, Bing; Zheng, Jiaojiao; Feng, Li; Du, Cheng; Jian, Shaoju; Yang, Weisen; Wu, Yimin A.; Jiang, Shaohua; He, Shuijian; Chen, Wei (Biochar (Online), 2022)
Developing effective electrodes with commercial-level active mass-loading (> 10 mg cm −2 ) is vital for the practical application of supercapacitors. However, high active mass-loading usually requires thick active mass layer, which severely hinders the ion/electron transport and results in poor capacitive performance. Herein, a self-standing biochar electrode with active mass-loading of ca. 40 mg cm −2 and thickness of 800 µm has been developed from basswood. The basswood was treated with formamide to incorporate N/O in the carbon structure, followed by mild KOH activation to ameliorate the pore size and introduce more O species in the carbon matrix. The as-prepared carbon monoliths possess well conductive carbon skeleton, abundant N/O dopant and 3D porous structure, which are favorable for the ion/electron transport and promoting capacitance performance. The self-standing carbon electrode not only exhibits the maximum areal/mass/volumetric specific capacitance of 5037.5 mF cm −2 /172.5 F g −1 /63.0 F cm −3 at 2 mA cm −2 (0.05 A g −1 ), but also displays excellent rate performance with 76% capacitance retention at 500 mA cm −2 (12.5 A g −1 ) in a symmetric supercapacitor, surpassing the state-of-art biomass-based thick carbon electrode. The assembled model can power typical electron devices including a fan, a digital watch and a logo made up of 34 light-emitting diodes for a proper period, revealing its practical application potential. This study not only puts forward a commercial-level high active mass-loading electrode from biomass for supercapacitor, but also bridges the gap between the experimental research and practical application. Graphical abstract Article Highlights Basswood-derived free-standing thick carbon electrodes were developed for supercapacitors. The capacitance performance was enhanced by pre-oxidation, solvothermal treatment and KOH activation. Supercapacitors assembled from the optimized electrode exhibited good rate performance and stability.